Answer:
9
Explanation:
Subtract
8
8
8
from both sides of the equation
−
2
+
8
=
−
1
0
-2x+8=-10
−2x+8=−10
−
2
+
8
−
8
=
−
1
0
−
8
-2x+8{\color{#c92786}{-8}}=-10{\color{#c92786}{-8}}
−2x+8−8=−10−8
2
Simplify
3
Divide both sides of the equation by the same term
4
Simplify
Solution
=
9Subtract
8
8
8
from both sides of the equation
−
2
+
8
=
−
1
0
-2x+8=-10
−2x+8=−10
−
2
+
8
−
8
=
−
1
0
−
8
-2x+8{\color{#c92786}{-8}}=-10{\color{#c92786}{-8}}
−2x+8−8=−10−8
2
Simplify
3
Divide both sides of the equation by the same term
4
Simplify
Solution
=
9